Essential References for Structural Analysis of the Peripheral Nervous System for Pathologists and Toxicologists. (January 2020) - Bolon, Brad; Krinke, Georg J.; Pardo, Ingrid D.
Toxicologic neuropathology for the peripheral nervous system (PNS) is a vital but often underappreciated element of basic translational research and safety assessment. Evaluation of the PNS may be complicated by unfamiliarity with normal nerve and ganglion biology, which differs to some degree among species; the presence of confounding artifacts related to suboptimal sampling and processing; and limited experience with differentiating such artifacts from genuine disease manifestations and incidental background changes. This compilation of key PNS neurobiology, neuropathology, and neurotoxicology references is designed to allow pathologists and toxicologists to readily access essential information that is needed to enhance their proficiency in evaluating and interpreting toxic changes in PNS tissues from many species.